On the Role of the Carboxyl Group to the Protective Effect of o-dihydroxybenzoic Acids to Saccharomyces cerevisiae Cells upon Induced Oxidative Stress - Nikolaos Nenadis; Efi Samara; Fani Th. Mantzouridou (MDPI AG, 2022)
In the present work, the role of the carboxyl group of o-dihydroxybenzoic acids (pyrocatechuic, 2,3-diOH-BA and protocatechuic, 3,4-diOH-BA) on the protection against induced oxidative stress in Saccharomyces cerevisiae was examined. Catechol (3,4-diOH-B) was included for comparison. Cell survival, antioxidant enzyme activities, and TBARS level were used to evaluate the efficiency upon the stress induced by H2O2 or cumene hydroperoxide. Theoretical calculation of atomic charge values, dipole moment, and a set of indices relevant to the redox properties of the compounds was also carried out in the liquid phase (water). Irrespective of the oxidant used, 2,3-diOH-BA required by far the lowest concentration (3-5 μM) to facilitate cell survival. The two acids did not activate catalase but reduced superoxide dismutase activity (3,4-diOH-BA>2,3-diOH-BA). TBARS assay showed an antioxidant effect only when H2O2 was used; equal activity for the two acids and inferior to that of 3,4-diOH B. Overall, theoretical and experimental findings suggest that the 2,3-diOH-BA high activity should be governed by metal chelation. In the case of 3,4-diOH BA, radical scavenging increases, and chelation capacity decreases. The lack of carboxyl moiety (3,4-diOH B) improves to radical scavenging, interaction with lipophilic free radicals, and antioxidant enzymes. The present study adds to our knowledge of the antioxidant mechanism of dietary phenols in biological systems.